The art of the game of chess - López de Segura, Ruy, active 16th century (The Catholic University of America Press, 2020)
"The first English translation of the 1561 book about chess, written for the court of Phillip II of Spain. Ruy López, who invented the important opening move that bears his name, is widely known as one of the most influential writers on chess theory"--